2020
DOI: 10.1084/jem.20190348
|View full text |Cite
|
Sign up to set email alerts
|

Qki is an essential regulator of microglial phagocytosis in demyelination

Abstract: The mechanism underpinning the regulation of microglial phagocytosis in demyelinating diseases is unclear. Here, we showed that the Quaking protein (Qki) in microglia was greatly induced by demyelination in the brains of both mice and humans. Deletion of the Quaking gene (Qk) in microglia severely impaired the clearance of myelin debris. Transcriptomic profiling indicated that depletion of Qki impaired total RNA levels and splicing of the genes involved in phagosome formation and maturation. RNA immunoprecipit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 64 publications
1
22
0
Order By: Relevance
“…As these gangliosides are prevalent on neuronal membrane, the upregulation of this key lysosomal regulator during a period of astrocyte maturation that covers synaptic pruning, suggests QKI might dynamically regulate aspects of local lysosomal function related to synaptic pruning by astrocytes and the subsequent clearance of this breakdown product. Indeed, a very recent report defined a similar role for QKI in microglia in clearance of myelin debris after experimentally induced demyelination 52 .…”
Section: Discussionmentioning
confidence: 97%
“…As these gangliosides are prevalent on neuronal membrane, the upregulation of this key lysosomal regulator during a period of astrocyte maturation that covers synaptic pruning, suggests QKI might dynamically regulate aspects of local lysosomal function related to synaptic pruning by astrocytes and the subsequent clearance of this breakdown product. Indeed, a very recent report defined a similar role for QKI in microglia in clearance of myelin debris after experimentally induced demyelination 52 .…”
Section: Discussionmentioning
confidence: 97%
“…Step 4: One of the prerequisites of effective remyelination is the phagocytosis of myelin debris (Step 1). Recent evidence shows that this process is facilitated by the upregulation of various transcripts such as Qki, Trem2 and Mertk, expressed by microglia and astrocytes (Cignarella et al, 2020; Ren et al, 2021; Shen et al, 2021). In addition, increased expression of other microglial genes (e.g., Lrp and Calr) facilitates phagocytosis and the removal of myelin debris (Olah et al, 2012).…”
Section: Using the Cpz Model To Investigate Microglial And Astrocytic...mentioning
confidence: 99%
“…Quaking is an RNA‐binding signaling protein that controls alternative splicing in vascular cell differentiation (Caines et al, 2019). The study by Ren et al (2021) rigorously analyzed the involvement of Qki in myelin debris clearance using multiple experimental approaches, including immunohistochemistry, Western blotting, transcriptomics, and transmission electron microscopy, demonstrating that deletion of the Qki gene (using an inducible conditional knockout; iCKO) preferentially impaired microglia‐mediated myelin debris clearance by affecting their phagocytic activity. Using the CPZ model, Ren et al (2021) first observed the activation of microglia by immunofluorescence staining of enhanced yellow fluorescent protein (Eyfp) expression in mice bearing Cx3cr1 CreER‐Eyfp allele (Eyfp labeled all Iba1 + microglia) in the corpus callosum.…”
Section: Microglia‐mediated Myelin Debris Clearancementioning
confidence: 99%
See 1 more Smart Citation
“…This binding site, termed the QKI response element (QRE), is frequently located in introns, as observed by various CLIP strategies (Hafner et al, 2010;Van Nostrand et al, 2020). QKI has been extensively studied in the context of oligodendrocyte maturation, cancer progression, immune cell function, and muscle cell differentiation as regulating pre-mRNA splicing, mRNA export, mRNA stability, miRNA maturation and circular RNA biogenesis (Conn et al, 2015;Darbelli & Richard, 2016;De Bruin et al, 2016;De Bruin et al, 2020;Fagg et al, 2020;Ren et al, 2021).…”
Section: Quakingmentioning
confidence: 99%